Percutaneous tracheostomy in Costa Rican intensive care units: multicenter epidemiology, practices, and immediate complications - Álvarez Aguilar, Pablo (2026)
Introduction: This study describes the epidemiological and clinical profile of ICU patients undergoing percutaneous tracheostomy in Costa Rica and identifies predictors of acute complications, addressing ongoing debates on timing, technique, and risk stratification. Methods: We performed a prospective multicenter cohort study in eight CCSS hospitals (2019–2022), including adult ICU patients undergoing percutaneous tracheostomy. Demographic, clinical, and procedural data were collected, and multivariable logistic regression identified predictors of complications. Results: A total of 516 patients were analyzed (mean age 53.2 ± 16.3 years; 68.2% male). The main indications were anticipated prolonged ventilation (32.4%), neurological deficits (26.7%), and ventilation >10 days (21.8%). The Ciaglia and Griggs techniques were used in 51.0% and 48.3% of cases, respectively. Capnography was applied in 74.2%, ultrasound in 17.7%, and bronchoscopy in 3.1%. First-pass success was achieved in 85.1%. Acute complications occurred in 28.3% of patients, predominantly minor bleeding (25.4%), while serious complications (airway loss, false passage, or bleeding requiring surgery) were rare (3.9%). No procedure-related deaths were observed. Independent predictors of complications included anticoagulation (OR 2.82), obesity (OR 2.10), coagulopathy (OR 2.29), prior neck surgery (OR 3.49), cervical immobilization (OR 4.68), and technical difficulty (OR 4.15 for any complication; OR 2.00 for serious complications). Airway management by physicians, compared with respiratory therapists, was also associated with higher risk (OR 1.52). Conclusions: Percutaneous tracheostomy was feasible in multiple ICUs of the CCSS with complication rates comparable to international cohorts. Risk factors for complications included anticoagulation and prior neck surgery. Wider adoption of adjunctive monitoring tools and structured multidisciplinary training may further enhance procedural safety. These findings should be interpreted in the context of an observational design and a broad definition of complications.